2022
DOI: 10.3389/fnagi.2022.1065904
|View full text |Cite
|
Sign up to set email alerts
|

The promise of multi-omics approaches to discover biological alterations with clinical relevance in Alzheimer’s disease

Abstract: Beyond the core features of Alzheimer’s disease (AD) pathology, i.e. amyloid pathology, tau-related neurodegeneration and microglia response, multiple other molecular alterations and pathway dysregulations have been observed in AD. Their inter-individual variations, complex interactions and relevance for clinical manifestation and disease progression remain poorly understood, however. Heterogeneity at both pathophysiological and clinical levels complicates diagnosis, prognosis, treatment and drug design and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Precision medicine will play a key role toward a personalized approach needed to treat complex neurodegenerative diseases. This has been steadily gaining traction for some time, but now with the advent of artificial intelligence, new generation genetics and multi-omics screenings (Baxter et al, 2021;Dong et al, 2021;Clark et al, 2022), paired with state-of-the-art technology, the field is approaching a point that personalized medicine could now become a reality. New departments focused on precision medicine are being formed at academic, governmental, non-profit and forprofit institutions around the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Precision medicine will play a key role toward a personalized approach needed to treat complex neurodegenerative diseases. This has been steadily gaining traction for some time, but now with the advent of artificial intelligence, new generation genetics and multi-omics screenings (Baxter et al, 2021;Dong et al, 2021;Clark et al, 2022), paired with state-of-the-art technology, the field is approaching a point that personalized medicine could now become a reality. New departments focused on precision medicine are being formed at academic, governmental, non-profit and forprofit institutions around the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Unsupervised integration of multi-omics datasets has been mainly used in primary research, including AD, PD and ALS studies [ 4 , 12 , 227 , 228 ]. Recently, this approach has been adopted by neurodegenerative disease related data mining studies.…”
Section: Towards Integrative Multi-omics and Systems Bioinformatics T...mentioning
confidence: 99%
“…In addition, data mining overcomes the technical challenges in conducting the initial experiments such as difficulty in obtaining precious tissue samples, stringent requirements in sample preparation, and high cost, while creating opportunities for new diagnostic and therapeutic strategies targeting neurodegenerative diseases. While single omics analyses have provided valuable disease mechanistic insights, recent studies have shown that integrative multi-omics analysis can help to define the connection and relationship among the different types of omics datasets to unravel brain networks regulating transitions from health to the development of neurological diseases and to classify clinically relevant subgroups to identify potential biomarkers [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-omics approaches can reveal not only how complex biomolecular profiles change in association with a disease, but also the relationships and correlations between distinct classes of biological molecules. Their potential for studying neurodegeneration has been previously described [24][25][26][27][28][29][30][31][32][33][34]. However, only recently has the deep molecular characterization of multiple cortical regions from diverse brain banks and cohorts been generated [2,3], enabling a more detailed and comprehensive examination of cross-omics data in AD.…”
Section: Introductionmentioning
confidence: 99%